BRAF V600E mutation as a novel mechanism of acquired resistance to ALK inhibition in ALK-rearranged lung adenocarcinoma: A case report. Issue 8 (26th February 2021) - Sui, Aixia; Song, Huiling; Li, Yitong; Guo, Litao; Wang, Kai; Yuan, Mingming; Chen, Rongrong
Abstract: Rationale: Patients with lung adenocarcinoma harboring EML4-ALK rearrangements respond well to multiple ALK tyrosine kinase inhibitors (TKIs). However, the tumor will invariably progress due to acquired resistance. Comprehensive genomic profiling appears to be a promising strategy to reveal the underlying molecular mechanisms of ALK-TKIs resistance. Patient concerns: A patient with right lung adenocarcinoma harboring an ALK rearrangement received targeted therapy with multiple ALK-TKIs. He sought for follow-up treatment after his disease progressed again. Diagnosis: The patient had a tumor diagnosed with stage I (T1bN0M0) lung adenocarcinoma. Interventions: Due to the surgical contraindication, the patient did not undergo surgical resection. Instead, he received crizotinib as the first-line therapy with the progression-free survival of 20 months. Then he switched to alectinib treatment, however the disease rapidly progressed again. Outcomes: Next-generation sequencing was performed and revealed that 7 somatic mutations were identified. Among them, 2 mutations, ALK I1171T and BRAF V600E, may be responsible for the resistance of this patient to ALK-TKIs. BRAF V600E mutation may explain the patient's resistance to lorlatinib. Lessons: We present a case of ALK -rearranged lung adenocarcinoma with acquired resistance to ALK inhibition, in which the BRAF V600E mutation is a novel resistance mechanism. This provides evidence that BRAF V600E mutation is one mechanism of ALK-TKI resistance.